Low level laser therapy in the treatment of aphthous ulcer - Vishal Anand; Minkle Gulati; Vivek Govila; Bhargavi Anand (Wolters Kluwer Medknow Publications, 2013)
Recurrent aphthous stomatitis (RAS) is one of the most common and painful ulcerative lesions of the oral cavity, but until now no cure has been recognized for it. Two patients diagnosed with minor RAS were treated in a single sitting with low level laser therapy using 940-nm diode laser. The lesions healed completely within 3-4 days and a follow-up for 1 showed no recurrence in these patients. According to the results of this study, low level laser therapy can decrease the healing time, pain intensity, size, and recurrence of the lesion in patients with minor RAS, and hence can be considered the most appropriate treatment modality for minor RAS, with greatest clinical effectiveness.